P-54 Was it worth it? intrathecal analgesia for cancer pain; the views of carers. (1st March 2017) - Huddart, Melanie; Patel, Nishi; Makins, Helen; Mitchell, Theresa; Gibbins, Jane L; Graterol, Juan; Stevens, Deborah; Perkins, Paul
Abstract : Background: Intrathecal Drug Delivery (ITDD) is known to reduce pain in patients where conventional systemic analgesia has been ineffective or intolerable. However more information about how this intervention affects quality of life (QOL) and function in those with advanced incurable cancer is required. Aim: To explore the views of bereaved carers regarding the physical and psychosocial effects of ITDD in patients with advanced incurable cancer. Methods: Qualitative interviews were undertaken with carers of deceased individuals who received ITDD (percutaneous, external system) as part of their pain management. Interviews were analysed using thematic analysis. Results: Eleven interviews were conducted in two United Kingdom centres with established ITDD services. The themes were: (1) 'making the decision to have the ITDD', family carers described very severe pain and/or sedation, in which the suffering individual would try anything; (2) 'timing and knowing they were having the best', ITDD and the associated increased access to pain and palliative care services, meant relatives felt everything possible was being done, making the situation more bearable; (3) 'was it worth it?', the perceived benefits were weighed up against the inconveniences and side effects of the ITDD; family carers judged the ITDD to be of overall benefit, despite side effects, where it had enabled the individual to be themselves through their final illness and dying phase. Conclusion: ITDD was perceived to be of greatest value when it improved QOL for patients by reducing pain and systemic side effects, thus enabling individuals to be themselves for as long as possible; under these circumstances significant side effects were judged to be acceptable. The family carers conveyed comfort in knowing that the patient was receiving what they felt was the best available management, support and specialist care. These findings should inform discussions between patients, physicians and palliative care teams around the management of severe uncontrolled pain in advanced malignancy.